Pedagogy, Situations, and Experiences in Havana: The Departamento de Intervenciones Públicas Between Intervention and Participant Observation - Francesca D'Andrea (piano b)
In the early 2000s, Havana witnessed the emergence of numerous artistic initiatives situated at the intersection of pedagogy and urban space interventions, characterized by a strong participatory approach. Many of these projects, developed within the Instituto Superior de Arte (ISA), aimed to engage a non-artistic audience and to experiment with collaborative dynamics within the groups themselves. This paper presents the activities and methodologies of the Departamento de Intervenciones Públicas (DIP), active from 2001 to 2004, based on research conducted from 2021 to 2024 between Cuba and Italy. The investigation relied primarily on private archival materials and conversations with the artists involved. The DIP conceived artistic practice as an ephemeral action, in which the often-unaware involvement of the local population acquired the value of an active field research. This experience helped shape a set of interventions grounded in social behavior as material for inquiry, contributing to a field of practice situated between art and anthropology that positioned Havana as a key center in the contemporary art landscape.